1996
DOI: 10.1111/j.1600-0447.1996.tb10629.x
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind multicentre comparison of mirtazapine and amitriptyline in elderly depressed patients

Abstract: A total of 115 elderly patients (60-85 years of age) with DSM III diagnosis of major depressive episode were randomly assigned to 6 weeks of treatment with either mirtazapine, 15-45 mg/day, or amitriptyline, 30-90 mg/day. Efficacy was assessed biweekly, using the Hamilton Rating Scale for Depression (HRSD) and Montgomery and Asberg Depression Rating Scale (MADRS) as primary outcome variables. The treatment with both drugs resulted in a similar reduction of total HRDS and MADRS scores, with no statistically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 26 publications
2
36
0
4
Order By: Relevance
“…Other than this one study, there are no other published placebo-controlled trials of mirtazapine in the elderly. Mirtazapine has also been compared with amitriptyline (Hoyberg et al, 1996) and paroxetine (Schatzberg et al, 2002). Although both studies found comparable efficacy between agents, in the paroxetinemirtazapine comparison, the mirtazapine group appeared to have a faster decrease in mean HAM-D (17 item) scores.…”
Section: Other Antidepressant Agentsmentioning
confidence: 99%
“…Other than this one study, there are no other published placebo-controlled trials of mirtazapine in the elderly. Mirtazapine has also been compared with amitriptyline (Hoyberg et al, 1996) and paroxetine (Schatzberg et al, 2002). Although both studies found comparable efficacy between agents, in the paroxetinemirtazapine comparison, the mirtazapine group appeared to have a faster decrease in mean HAM-D (17 item) scores.…”
Section: Other Antidepressant Agentsmentioning
confidence: 99%
“…Unlike other pharmacogenetic studies involving antidepressants, this study used a single antidepressant rather than multiple medications, which may reduce the variation in the pharmacological mechanism of action among individuals (Behnke et al, 2003;Bruijn et al, 1999;Hoyberg et al, 1996;Leinonen et al, 1999) and minimize the effects of other biological differences (Haapasalo-Pesu et al, 2004;Murphy et al, 2004). Depression is a multifactoral disorder and probably involves multiple genes.…”
Section: Discussionmentioning
confidence: 95%
“…Reboxetine showed similar efficacy to imipramine in depressed elderly patients [103,104]. Mirtazapine has shown similar efficacy to amitriptyline in elderly depressed patients [44]. In a placebo-controlled study in depressed patients over the age of 55, mirtazapine was superior to trazodone [105].…”
Section: Efficacymentioning
confidence: 93%
“…Efficacy A number of placebo-controlled and active comparator studies, mainly using amitriptyline or imipramine, have demonstrated the efficacy of tricyclic antidepressants (TCAs) in the elderly [40][41][42][43][44][45][46][47]. In patients with depression and Alzheimer's disease, clomipramine [48], but not imipramine [49], has shown superiority to placebo.…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%